2019
DOI: 10.14254/2071-8330.2019/12-4/7
|View full text |Cite
|
Sign up to set email alerts
|

Testing mean-reversion in agricultural commodity prices: Evidence from wavelet analysis

Abstract: This study examines the validity of the random walk hypothesis for some selected soft agricultural commodity prices within the context of heterogeneous market hypothesis and mean reversion hypothesis. The study employs a battery of traditional unit root tests, GARCH-based models and a novel frequency-based wavelet analysis to analyze daily data sourced from 6th of Jan 1986 to 29 th Dec 2018. Contrary to other existing studies that employed only traditional time domain unit root tests, our results reveal that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…This proposition was hatched around 1883. Ever since the unveiling of this proposition, followers of this view have expressed mixed opinions ( Gatsi et al., 2019 ; Manyeki and Kotosz, 2017 ; Keho, 2017 ; Lawal et al., 2020 ; Asaleye et al., 2020 ; Lawal et al., 2019 ; Babajide et al., 2020 ; Olanrele et al., 2020 ; Aktan, 2017 ; Ifeyinwa, Idenyi, Chibuzor & Agbi, 2016; Eze, 2016 ; Salwindi and Seshamani, 2016 ; Dahunsi et al., 2019 ; Moore, 2016 ; Atasoy and Gur, 2016 ; Ampah and Kotosz, 2016 ; Magazzino et al., 2015 ; Funashima, 2015 ). Among early versions that propelled dichotomization of WP are that of Peacock and Wiseman (PW) (1961) , Musgrave (1969) , Gupta (1967) , Goffman (1968) , Peacock & Wiseman shared version (1967) , among others; each explaining its own version of the proposition based on their scholarly standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…This proposition was hatched around 1883. Ever since the unveiling of this proposition, followers of this view have expressed mixed opinions ( Gatsi et al., 2019 ; Manyeki and Kotosz, 2017 ; Keho, 2017 ; Lawal et al., 2020 ; Asaleye et al., 2020 ; Lawal et al., 2019 ; Babajide et al., 2020 ; Olanrele et al., 2020 ; Aktan, 2017 ; Ifeyinwa, Idenyi, Chibuzor & Agbi, 2016; Eze, 2016 ; Salwindi and Seshamani, 2016 ; Dahunsi et al., 2019 ; Moore, 2016 ; Atasoy and Gur, 2016 ; Ampah and Kotosz, 2016 ; Magazzino et al., 2015 ; Funashima, 2015 ). Among early versions that propelled dichotomization of WP are that of Peacock and Wiseman (PW) (1961) , Musgrave (1969) , Gupta (1967) , Goffman (1968) , Peacock & Wiseman shared version (1967) , among others; each explaining its own version of the proposition based on their scholarly standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…The OFID/IIASA research found that in developing countries, only small rural development benefits would be obtained. Furthermore, in terms of percentage increase in value added by 6-8% in the former and only 3% in the latter, by the year 2030 estimates, agriculture in highly industrialized countries profit comparatively more than in developing countries (Lawal et al, 2019).…”
Section: Biofuels Versus Agriculturementioning
confidence: 99%
“…According to the theory, a certain number of macroeconomic factors affect stock price, altering stock price behaviour. The theoretical connection between stock prices and foreign exchanges can be classified into three main approaches: Flow-oriented approah, an approach that explains that currency fluctuations cause stock price changes by changing company cost structures across international exchanges; stockoriented approaches which found that the causality flows constitute exchange price stock through fluctuation in both foreign capital inflows and outflows due to price fluctuations; and the Indifferent approach that states neutrality of relationship between asset prices and other fundamentals Rigobon and Sack, 2004;Lawal et al, 2019;Dornbusch and Fisher, 1980;Dreger and Reimers, 2016. The theoretical connection between oil prices and the movement in stock prices is rooted in a theory of substitution. In this regard, it was expected that the rise in oil prices would raise the production cost which would affect income negatively.…”
Section: Theoretical Structurementioning
confidence: 99%